Research on the axial force-slip characteristics of permanent magnetic eddy current Frictional torque limiter - Yuting WANG; Hong ZHANG (Meitan kexue jishu, 2023)
In view of the current situation of short life and poor reliability of the overload protection device of friction moment limiter in coal mine machinery, a new high-power fast breaking permanent magnet eddy current friction Moment limiter (PMEFTL) is proposed, which is composed of permanent magnet eddy current transmission mechanism and friction clutch. Its working principle is as follows: The magnet static magnetic attraction of permanent magnet eddy current drive mechanism between the plate and the conductor plate exerts axial pressure on friction clutch friction plate, forming friction limit of torque transmission torque, with the aid of instant overload master-slave friction plate relative slip control of axial repulsion between conductor plate and the magnet plate, friction plate from and quickly cut off the transmission system. Firstly, the eddy current magnetic field mathematical description and finite element model of PMEFTL are established. Based on transient magnetic field analysis, the axial force generation mechanism of permanent magnet eddy current mechanism in PMEFTL is studied, and the axial force maxwell tensor form of PMEFTL and the torque calculation equation of friction torque limit are proposed. The results show that the total axial force of the permanent magnet eddy current mechanism is composed of the axial force of the back iron and that of the conductor disk, along with the increase of slip, back iron axial force is always characterized by gravity and gradually reduce, conductor plate of axial force is always characterized by repulsion, and gradually increase, the total axial force is gradually by attraction into a repulsive force, and static attraction point and disengage speed point two feature points. The transmitted torque of PMEFTL is proportional to the total axial force. Before overload skidding, the transmitted torque is equal to the static friction force of the friction pair; after overload skidding, the transmitted torque is composed of friction torque and electromagnetic torque. Secondly, the influencing factors of axial force slip characteristics of PMEFTL are studied based on three-dimensional finite element method. It is concluded that increasing the thickness and duty cycle of permanent magnet, increasing the number of conductor grooves, and decreasing the duty cycle of conductor grooves can improve the static attraction and improve the transmission ability of PMEFTL. The detachment speed point is related to the relative relationship between axial attraction and axial repulsion force. On the premise that static attraction is determined, the detachment speed point can be adjusted by adjusting the duty cycle of conductor cogs and the number of conductor cogs. Finally, the design parameters of the thickness, duty cycle, poles of the permanent magnet and the duty cycle and the number of slots of conductor plate of 375 kW PMEFTL are optimized. Compared with the primary parameters, the static attraction is increased by 90% and the amount of friction pairs is reduced by nearly one time after optimization. The application of PMEFTL in coal mine machinery will effectively improve the reliability and service life of the transmission system, reduce the corresponding downtime and maintenance work, and improve the production efficiency